Mental Load and Its Compensation by Physical Activity in Adolescents at Secondary Schools - Svozil, Zbyněk; Frömel, Karel; Chmelík, František; Jakubec, Lukáš; Groffik, Dorota; Šafář, Michal (Central European journal of public health, 2015)
AIM: Sedentary behaviour and increasing mental load in adolescents is one of the major health problems of the contemporary youth. The aim of the study is to analyze the associations between mental load and physical activity (PA) in adolescents in school-day segments. METHODS: 381 adolescents (120 boys, 261 girls) took part in the research which was conducted in 19 secondary schools in the Czech Republic. Participants throughout the whole day (1-3 days) wore an ActiTrainer accelerometer that monitors PA and heart rate (HR). The reports covered 727 school days. The participants were divided into two groups with lower and higher mental load. RESULTS: Boys and girls with higher mental load in lessons do not compensate this load in neither volume nor intensity of PA during recess in greater amount than those who had lower mental load. In the individual school-day segments (apart from the time before school) no significant differences between the groups were found. CONCLUSION: When creating a habit of immediate compensation for mental load in lessons by PA, it is necessary to pay attention to boys and girls with higher mental load in lessons. The adoption of the habit should be supported by adequate physical literacy of both students and teachers and by changes in the school programme.
Keywords: pohybová aktivita; duševní procesy; Humans; Sedentary Behavior; physical education; Female; health education; sedavý životní styl; lidé; Mental Processes; recess; ženské pohlaví; Male; school physical activity; Adolescent; akcelerometrie; recommendation; Czech Republic; Accelerometry; Motor Activity; Česká republika; mužské pohlaví; mladiství